Erbium-activated silica-titania planar waveguides prepared by rf-sputtering - Ronchin, Sabina; Chiasera, Alessandro; Montagna, Maurizio; Rolli, Raffaella; Tosello, Cristiana; Pelli, Stefano; Righini, Giancarlo C.; Gonçalves, Rogeria R. [UNESP]; Ribeiro, Sidney [UNESP]; De Bernardi, Carlo; Pozzi, Fabio; Duverger, Claire; et al. (SPIE, the international society for optics and photonics, 2001)
Erbium-activated silica-titania planar waveguides were prepared by rf-sputtering technique. The films were deposited both on v-SiO2 and silica-on-silicon substrates obtained by plasma-enhanced chemical vapor deposition. The refractive index, the thickness and the total attenuation coefficient of the waveguides were measured by prism coupling technique. Scanning electron microscopy was used to analyze the morphology of both substrates and waveguiding film. Energy Dispersive Spectrometry was performed in order to obtain a compositional analysis. Roughness measurements were carried out by means of a stylus profilometer. After thermal annealing at 600°C for 6 hours the waveguides exhibited several well confined TE and TM propagating modes at 633 nm and one mode at 1550 nm. The attenuation coefficient at 1550 nm was 0.9 and 0.7 dB/cm for the films deposited on silica-on-silicon and the v-SiO2 substrates, respectively. Structural information about the deposited films were obtained by waveguide Raman spectroscopy. Waveguide luminescence spectroscopy was used to study the 4I13/2 → 4I15/2 transition of Er3+ ion. The emission at 1530 nm was observed at room temperature upon continuous wave excitation at 514.5 nm. A lifetime of 3.7 ms for the metastable 4I13/2 level was measured.
Keywords: Erbium; Optical properties; Photoluminescence; Planar waveguides; Raman spectroscopy; Rf-sputtering; SiO2-TiO2